The addition of feed additive in beef cattle ration on in vitro fermentation characteristics. Issue 1 (November 2021) - Hartina, W A; Ridwan, R; Diapari, D; Fidriyanto, R; Jayanegara, A
Abstract: The effects of feed additives are increasing feed digestibility, balance of rumen microbial community, stimulating the immune response and livestock productivity. This study aimed to determine the effects of feed additives combination in the rumen fermentation. The method used in this study was a block randomized design with 9 treatments and 3 replications. The experiment using Theodorou In vitro method for 48 hours with parameters such as pH, kinetics gas and methane production, DMD, OMD, NH3, and partial VFA. The treatment were P0; control (Basal Diet 70% Concentrate + 30% Forages), P1; P0 + Premix, P2; P1 + Probiotic, P3; P1 + Enzyme, P4; P1 + Plant Extract, P5; P1 + (Probiotics + Enzyme), P6; P1 + (Probiotics + Plant Extract), P7; P1 + (Probiotic + Enzyme + Plant Extract), and P8; P1 + (Enzyme + Plant Extract). The results showed kinetics gas, methane production, NH3, and partial VFA were significantly affected (P <0.05), while the value of pH, DMD, and OMD was not significant. In conclusion, the addition of mix feed additives can affect the kinetics gas and methane production. However, it does not affect the level of pH, dry matter and organic matter digestibility.